Avaliação das condutas de biossegurança em laboratórios de prótese dentária de João Pessoa, PB, Brasil - da Silva, Manoela Capla de Vasconcellos dos Santos [UNESP]; Cartaxo, José Ulisses Queiroga; Arioli Filho, João Neudenir [UNESP]; Batista, André Ulisses Dantas (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2010)
Objective: To evaluate the biosecurity measures adopted in dental prosthesis laboratories of the city of João Pessoa, PB, Brazil with respect to prosthetic works sent by dentists. Method: Twenty-five dental prosthesis technicians (DPT) of the city of João Pessoa, PB, filled out a questionnaire referring to their knowledge of the biosecurity principles, disinfection of impressions and other prosthetic items, and the use of individual protection equipment (IPE). Results: Although 92% of the interviewees believed in the possible occurrence of cross-infection between dental prosthesis laboratories and dental offices, 64% declared that the prosthetic works received in their laboratories do not undergo any disinfection procedure. It was also observed that, for disinfection of impressions and stone casts, the chemical substances are not used as recommended by the manufacturers or are innocuous to microorganisms. Regarding the use of IPE, 60% of the DPT used mask, but only 4% used gowns. With respect to the measures taken regarding the impressions received from dental offices, 56% of the interviewees only wash them in running tap water, and 56% of the stone casts that arrive at the laboratory are not disinfected in any way. Conclusion: There is a need for more motivation and instructions to DPT regarding the prevention of cross-contamination during sending and receiving of prosthetic works between dental prosthesis laboratories and dental offices because the DPT evaluated in this study were found negligent with respect to disinfection procedures.
Evaluation of the biosecurity measures adopted in dental prosthesis laboratories of the city of João Pessoa, PB, Brazil
Keywords: Disinfection; Infection control; Prosthesis